PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN BENTO CAFÉ YOGYAKARTA - Arief Rahman Wahid; Ignatius Soni Kurniawan; Eko Yulianto (Universitas Bina Taruna Gorontalo, 2023)
This study aims to determine the effect of organizational culture and the work environment on job satisfaction. This research is a quantitative study with primary data taken using a questionnaire. The sample determination technique uses a census technique. The population used was 50 employees of Bento Cafe Yogyakarta. Data analysis included validity and reliability tests, classical assumption tests, and multiple regression analysis using the SPSS software application. The results of the analysis show that organizational culture and work environment have a significant effect on employee job satisfaction, partially and simultaneously.